P-090 EMERGENCY INTRAPERITONEAL ONLAY MESH REPAIR OF INCARCERATED VENTRAL E INCISIONAL HERNIA. (13th October 2022) - Garbarino, S; Latham, L; Marzorati, A; Gianazza, S; Zullo, A; Scorza, A; Costantini, D; Ballabio, A; Inversini, D; Ietto, G; Carcano, G
Abstract: Aim: Abdominal wall hernia surgery is the frequent surgical operation. Incarceration and strangulation are the complications for patients going to emergency surgery clinics.Laparoscopic approach in emergency is controversial. IPOM treatment permits safe hernia reduction, accurate abdominal exploration, diagnosis and treatment of unknown hernia. Material and Methods: in one year, we operated 12 urgent ventral hernia patients with IPOM technique. All patientsshowed hemodynamic stability. We evaluated safety of hernia reduction, conversion rate, operative time, hospital stay, and prosthesis infection. Results: Nine patients underwent surgery for incarcerated incisional hernia, 3 patients for primary incarcerated ventral hernia. We used a laparoscopic approach. In 10 cases, we placed an intraperitoneal mesh. In two cases, we converted to open surgery, because of small bowel injury. It was never necessary to perform Intestinal resection for strangulated hernia.Contents of hernia sacs were omentum (7 patients), large bowel (1 patients), 4 omentum and small bowel (4 patients). Patients presented signs of small bowel obstruction. Average size of the defect was 6cm.Average operative time was 91 min, the mean post-operative hospital stay was 3.5 days. Post-operative complications weren't recorded. There wasn't mortality. During the follow-up none patients had mesh infection or hernia recurrence. Conclusion: In emergency the Intraperitoneal Onlay Mesh Repair of Incarcerated Ventral and Incisional Hernia allowed safe adesiolysis, bowel reduction. Laparoscopic approach was associated to low post-operative complications even in emergency setting.